N-acetyl-L-cysteine treatment reduces beta-cell oxidative stress and pancreatic stellate cell activity in a high fat diet-induced diabetic mouse model - Schuurman, Meg; Wallace, Madison; Sahi, Gurleen; Barillaro, Malina; Zhang, Siyi; Rahman, Mushfiqur; Sawyez, Cynthia; Borradaile, Nica; Wang, Rennian (Frontiers in Endocrinology, 2022)
Obesity plays a major role in type II diabetes (T2DM) progression because it applies metabolic and oxidative stress resulting in dysfunctional beta-cells and activation of intra-islet pancreatic stellate cells (PaSCs) which cause islet fibrosis. Administration of antioxidant N-acetyl-L-cysteine (NAC) in vivo improves metabolic outcomes in diet-induced obese diabetic mice, and in vitro inhibits PaSCs activation. However, the effects of NAC on diabetic islets in vivo are unknown. This study examined if dosage and length of NAC treatment in HFD-induced diabetic mice effect metabolic outcomes associated with maintaining healthy beta-cells and quiescent PaSCs, in vivo. Male C57BL/6N mice were fed normal chow (ND) or high-fat (HFD) diet up to 30 weeks. NAC was administered in drinking water to HFD mice in preventative treatment (HFDpNAC) for 23 weeks or intervention treatment for 10 (HFDiNAC) or 18 (HFDiNAC+) weeks, respectively. HFDpNAC and HFDiNAC+, but not HFDiNAC, mice showed significantly improved glucose tolerance and insulin sensitivity. Hyperinsulinemia led by beta-cell overcompensation in HFD mice was significantly rescued in NAC treated mice. A reduction of beta-cell nuclear Pdx-1 localization in HFD mice was significantly improved in NAC treated islets along with significantly reduced beta-cell oxidative stress. HFD-induced intra-islet PaSCs activation, labeled by αSMA, was significantly diminished in NAC treated mice along with lesser intra-islet collagen deposition. This study determined that efficiency of NAC treatment is beneficial at maintaining healthy beta-cells and quiescent intra-islet PaSCs in HFD-induced obese T2DM mouse model. These findings highlight an adjuvant therapeutic potential in NAC for controlling T2DM progression in humans.